The Effect of Murattal To Relieve Dysmenorrhea Pain in Female Students - Qanita Chairun Nissa; Neni Nuraeni; Hani Handayani (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Dysmenorrhea is menstruation pain that would interfere women’s activities. Murattal is a non-pharmacological technique that may relieve menstruation pain. The aim of this research was to find the effect of Murattal in relieving dysmenorrhea for female student of SMPN 12 Tasikmalaya. This research used quasi-experiment with pre-posttest and control group design. Respondents were selected using purposive sampling technique. This study involved 15 students in a group treatment and 15 students in a group control used technique purposive sampling. The instrument of this study was Numeric Rating Scale (NRS) Instrument. Respondents listened Murattal Surah Ar-Rahman. Data were analyzed using paired T-Test also used. The result found that there was an effect of Murattal to relieve dysmenorrhea pain for female student of SMPN 12 Tasikmalaya, with ρ value 0,000. The conclusion, Murattal is effective to relieve dysmenorrhea. There is a need of developing other non-pharmacology interventions to relive dysmenorrhea Keywords: Dysmenorrhea, Murottal, Pain